2016
DOI: 10.1016/j.chemosphere.2016.02.036
|View full text |Cite
|
Sign up to set email alerts
|

PPCPs in Jiulong River estuary (China): Spatiotemporal distributions, fate, and their use as chemical markers of wastewater

Abstract: The occurrence and fate of 50 pharmaceuticals and personal care products (PPCPs) were investigated in the surface water of Jiulong River estuary in the southeast of China in spring, wet season, summer, autumn and winter. Results demonstrated a wide distribution of PPCPs in Jiulong River estuary, where 34 PPCPs were detected at least once and 5 PPCPs were detected in all the samples, including caffeine, diclofenac, metoprolol, methyl paraben, and propyl paraben. Spatial and seasonal variations were observed. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(37 citation statements)
references
References 37 publications
4
33
0
Order By: Relevance
“…To be noticed, although the treatment processes are different among the seven WWTPs, the consistent high removal efficiencies of BPA, BPF, and BPS, together with the consistent low removal efficiencies of BPAF and BPE over 7 days indicate that BPs can be applied as sewage markers to designate the direct discharge of untreated wastewater into the surface water (Lv et al 2014, Nakada et al 2008, Sun et al 2016b. As discussed in Section 3.2, due to the strong evidence on BPA's industrial origin, BPA can be used as the industrial sewage marker.…”
Section: Removal Efficiencies Of Dissolved Bps In the Wwtpsmentioning
confidence: 99%
“…To be noticed, although the treatment processes are different among the seven WWTPs, the consistent high removal efficiencies of BPA, BPF, and BPS, together with the consistent low removal efficiencies of BPAF and BPE over 7 days indicate that BPs can be applied as sewage markers to designate the direct discharge of untreated wastewater into the surface water (Lv et al 2014, Nakada et al 2008, Sun et al 2016b. As discussed in Section 3.2, due to the strong evidence on BPA's industrial origin, BPA can be used as the industrial sewage marker.…”
Section: Removal Efficiencies Of Dissolved Bps In the Wwtpsmentioning
confidence: 99%
“…In recent years, pharmaceuticals and personal care products (PPCPs) and artificial sweeteners (ASs) have been proposed as more definitive wastewater indicators due to their anthropogenic origin and ubiquity in wastewater, surface water and even groundwater (Benotti and Brownawell 2007, Buerge et al 2003, Clara et al 2004, Daneshvar et al 2012, Glassmeyer et al 2005, Nakada et al 2008, Sun et al 2016b, Tran et al 2014a, Tran et al 2014b, Young et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is useful to combine conservative indicators which are recalcitrant in wastewater treatment plants (WWTPs) with liable indicators which are susceptible to biodegradation in WWTPs in identifying contamination source of treated or untreated wastewater (e.g. sewer leakages, combined sewer overflow, and illegal discharges) (Kasprzyk-Hordern et al 2009a, Lv et al 2014, Sun et al 2016b.…”
Section: Introductionmentioning
confidence: 99%
“…Parabens can be detected in wastewater, water, sediment, soil, human urine, blood, and adipose tissue (2,(4)(5)(6)(7)(8). Studies conducted in Canada (9), the United Kingdom (10), France (11), and China (12), reported the occurrence of parabens in municipal wastewater. There are studies suggesting that in the conventional WWTPs, these chemicals are not completely removed from the water cycle (8,(13)(14)(15) and this issue remains a challenging problem due to its complex matrices.…”
Section: Introductionmentioning
confidence: 99%